An industrial burner for co-combustion of natural gas with hydrogen - Świątkowski, Bartosz; Hercog, Jarosław; Kiedrzyńska, Aleksandra; Bocian, Paweł (Instal, 2021)
The article presents a prototype of an industrial burner with a power of 100kW, adapted to the co-combustion of natural gas with hydrogen (up to 50% by volume). The burner concept was developed at the Institute of Power Engineering Research using the CFD numerical modelling method. Numerical calculations were carried out for several technical concepts of the burner in order to select the most promising solution. The burner prototype was tested in an experimental stand located in the laboratory of the Institute of Power Engineering. As a result of this process, a 100kW burner model was successfully developed and experimentally verified. This burner can be used in high-temperature technological processes, offering a solution for the future transformation towards a climate-neutral industry.